The Existence of the Yellow Book in the Digital Era: Study in Dayah Aceh - Iin Meriza; Asra Febriani; Mutia Tisa; Muhammad Riza Nurdin (IAIN Padangsidimpuan, 2022)
The existence of the yellow book is very important for Islamic boarding schools or dayahs in Aceh. Every religious lesson must use the yellow book as the main reference for teachers in teaching. The yellow book has been used for centuries in the study of dayah. However, the existence of internet media in the current digital era has an effect on learning patterns in the dayah environment. The yellow book as a learning resource in the dayah faces the challenges of the digital era media that is able to answer various people's problems quickly. In the digital era, the public and students can access information related to Islamic teachings via the internet quickly, cheaply and easily. The purpose of this study is to find out and describe the existence of the yellow book in the digital era (study in dayah aceh). This research is a field research with a qualitative descriptive method. The results show that the yellow book still exists in the current digital era and remains a mandatory reference in the dayah curriculum, but the progress of the digital era continues to color the pesantren curriculum treasures with the finding that Guree Dayah uses the Maktabah Syamilah feature as a supporting reference. Furthermore, in responding to advances in information technology, dayah utilizes the internet as a medium of da'wah and socialization of dayah as well as reviewing legal issues encountered by the public on the internet by referring to the yellow book